2004
DOI: 10.1007/s00335-003-2270-3
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of a seizure susceptibility locus on mouse Chromosome 1: nomination of Kcnj10 as a causative gene

Abstract: Previous quantitative trait loci (QTL) mapping studies document that the distal region of mouse Chromosome (Chr) 1 contains a gene(s) that is in large part responsible for the difference in seizure susceptibility between C57BL/6 (B6) (relatively seizure-resistant) and DBA/2 (D2) (relatively seizure-sensitive) mice. We now confirm this seizure-related QTL ( Szs1) using reciprocal, interval-specific congenic strains and map it to a 6.6-Mb segment between Pbx1 and D1Mit150. Haplotype conservation between strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(52 citation statements)
references
References 44 publications
4
48
0
Order By: Relevance
“…It has previously been established that genetic background can considerably affect the seizure thresholds of mice. Loci responsible for strain differences in susceptibility to seizures, triggered by chemoconvulsants, such as kainic acid, or non-pharmacological manipulations, have been mapped to specific mouse chromosomes (Ferraro et al, 1997, 2001, 2004, 2007a,b, 2010, 2011; Todorova et al, 2006). The identified genomic loci map to chromosomes 1, 2, 4, 5, 7, 10, 11, 12, 15 and 18 with the highest density on chromosomes 1, 5, 7, and 10 where loci from several different crosses coincide.…”
Section: Mouse Models Of Epilepsy: Genetic Heterogeneitymentioning
confidence: 99%
“…It has previously been established that genetic background can considerably affect the seizure thresholds of mice. Loci responsible for strain differences in susceptibility to seizures, triggered by chemoconvulsants, such as kainic acid, or non-pharmacological manipulations, have been mapped to specific mouse chromosomes (Ferraro et al, 1997, 2001, 2004, 2007a,b, 2010, 2011; Todorova et al, 2006). The identified genomic loci map to chromosomes 1, 2, 4, 5, 7, 10, 11, 12, 15 and 18 with the highest density on chromosomes 1, 5, 7, and 10 where loci from several different crosses coincide.…”
Section: Mouse Models Of Epilepsy: Genetic Heterogeneitymentioning
confidence: 99%
“…Recent studies showed that loss-of-function mutations of the human gene ( KCNJ10 ) encoding Kir4.1 channels are responsible for the SeSAME/EAST syndrome, an autosomal recessive disorder characterized by seizures, sensorineural deafness, ataxia, intellectual disability and electrolyte imbalance (Bockenhauer et al, 2009; Scholl et al, 2009; Reichold et al, 2010). Genetic variations of KCNJ10 have also been related to epilepsy (Buono et al, 2004; Ferraro et al, 2004; Lenzen et al, 2005; Dai et al, 2015), a group of neurological diseases characterized by seizure disorders. Other diseases associated to Kir4.1 channels include spinocerebellar ataxia (Gilliam et al, 2014), autism (Sicca et al, 2011), Alzheimer disease (Wilcock et al, 2009), and Huntington disease (Tong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that mice models that lacked the Slc26a4 gene ( Slc26a4 −/− ) did not express Kcnj10 and that lack of this protein led to the loss of the endocochlear potential via endolymphatic acidification and Ca 2+ absorption inhibition [25,26] which may be the direct cause of deafness in Pendred syndrome. Variants of KCNJ10 have also been considered as a risk factor for seizure susceptibility in genetic association studies [27] and biallelic mutations in KCNJ10 in humans are known to cause a syndromic form of hearing loss, EAST syndrome (epilepsy, ataxia, sensorineural deafness and renal tubulopathy) [28]. …”
Section: Introductionmentioning
confidence: 99%